DBU‐Mediated [3+2] Cycloaddition Reactions of Donor–Acceptor Cyclopropanes with Nitromethane: Efficient Strategy for the Construction of Isoxazole Skeletons. Issue 14 (20th April 2016) - Xue, Shuwen; Liu, Jiaming; Wang, Cunde
Abstract: A new DBU‐mediated [3+2] cycloaddition reaction has been developed using readily available donor–acceptor cyclopropanes and nitromethane. This approach provides a straightforward and efficient route to the construction of polysubstituted isoxazole scaffolds in high yields. Abstract : Polysubstituted isoxazole‐5‐carboxylates were synthesized by DBU‐mediated [3+2] cycloaddition reaction of readily available donor–acceptor cyclopropanes and nitromethane.